5y+5+(2y+4)=11y-15

Simple and best practice solution for 5y+5+(2y+4)=11y-15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5y+5+(2y+4)=11y-15 equation:



5y+5+(2y+4)=11y-15
We move all terms to the left:
5y+5+(2y+4)-(11y-15)=0
We get rid of parentheses
5y+2y-11y+4+15+5=0
We add all the numbers together, and all the variables
-4y+24=0
We move all terms containing y to the left, all other terms to the right
-4y=-24
y=-24/-4
y=+6

See similar equations:

| 12v-14+3v=1 | | s/6-12=-8 | | 4x+3=(7x-8)+(x+3) | | r/2-8=8 | | m/3+16=9 | | 8=2x+6x | | 11g-7=59 | | 10(g+5)=2(g+4) | | 8c=12- | | 4x+3(x-1)=2(x-3)+9 | | 10x-7=15x-8 | | b-3/16=5/16b= | | 4(8y+4)-17=-2(4y-8) | | 4b+6=46 | | q(q-14)(4q-7)=0 | | 4(s+5)=32 | | (2x+8)/6+8=x+4 | | 2x+2+30+3x=0 | | x+(x+30)+2x= | | 16x-3=10x+18 | | x(x+5)=73 | | 3.4+x=18 | | 9-1/3=5/3n | | N^=5n | | 10x–15=85 | | 3(3x−1)=9x+7 | | (2x-8)=(3x-12) | | H(4)=-16(4)^2+68t+2 | | 2/3m-5=13 | | 3.8x-8.5=10.5 | | 9u+8u=2^0 | | 2.5(2z+5)=5(5(z+2.5) |

Equations solver categories